Comparison of the population occlusal characteristics in 3 Brazilian regions (Research, Society and Development, 2020)
The objective of this work was to determine the prevalence of individual traits of malocclusion in a sample of three Brazilian regions orthodontic patients and to detect interregional population differences in the prevalence of certain occlusal characteristics.  The present study was based on the examination of dental casts, intraoral photographs and panoramic radiographs of 947 orthodontic patients from 3 cities: 363 from Fortaleza (CE), 270 from Maringá (PR) and 314 from Bauru (SP), respectively, representing the Northeast, South and Southeast Brazilian regions. The relationship of the first maxillary and mandibular molars according to Angle’s classification, overjet, overbite, crowding, posterior crossbite and maxillary median diastema were examined. The chi-square and ANOVA tests were used to determine potential differences in the distribution of malocclusion when stratified Brazilian regions. Class I malocclusion was found in 499 (52.69%), Class II in 395 (41.71%) and Class III malocclusion in 53 (5,59%) subjects of all examined. Deep overbite (3.59%), midline diastemas (5.17%) and posterior crossbite (4.75%) were observed more frequently in Bauru; however, in Maringá, normal overbite (13.3%) and open bite (4.75%) were more prevalent. The results of this study showed that Class I malocclusion was the most prevalent, followed by Class II and Class III malocclusions. These occlusal relationships evaluated in the three Brazilian regions follow the same pattern of frequency as the result presented by the general population of the sample.